Comparative genome-wide analysis of CAD (Cinnamyl Alcohol Dehydrogenase) gene family in Medicago truncatula and Lotus japonicus and their expression profiles in response to various abiotic abiotic stresses - Mst. Sumaiya Khatun; Fatema Tuz Zohra; Pollob Shing; Md Shohel Ul Islam; Shaikh Mizanur Rahman; Md. Abdur Rauf Sarkar (PLoS ONE, 2026)
The CAD (Cinnamyl Alcohol Dehydrogenase) gene family is a key determinant for lignin biosynthesis in plants. In legumes, CAD enzymes are involved in the development of vascular tissues such as xylem and Casparian strip and they contribute to the production of antimicrobial and antifungal compounds. Thereby, it offers defense against pathogens and pests. Despite their biological significance, a comparative genome-wide analysis of the CAD gene family in Medicago truncatula and Lotus japonicus has not been explored. Therefore, we conducted a comparative genome-wide study to investigate the characteristics and potential role of CAD genes in these two model legume species. A total of 51 CAD genes were identified in M. truncatula ( MtCAD ) and 35 in L. japonicus ( LjCAD ). The CAD proteins are prominently characterized by ADH_N and ADH_zinc_N domains that were distributed in 8 and 6 chromosomes of MtCAD and LjCAD , respectively. Structural organization and conserved motif analysis indicated notable similarities between MtCAD and LjCAD proteins. However, considering the ancestry and functionality and based on the evolutionary analysis, LjCAD showed more similarities with Arabidopsis than MjCAD . Gene duplication analysis identified twelve duplicated gene pairs in MtCAD and eight in LjCAD, including both tandem and segmental duplication events . Most MtCAD and LjCAD were found in the cytoplasm with some of the cis -acting regulatory elements associated with stress responses. Gene Ontology annotation suggested that most MtCAD genes were associated with biological processes whereas LjCAD genes are mainly enriched in molecular functions. Both MtCAD and LjCAD showed potential roles in secondary metabolite production. Three substantial transcription factor families such as bZIP, C2H2, and ERF and several unique microRNAs were predicted to target MtCAD and LjCAD in regulating their gene expression against certain abiotic stressors for instance cold, freezing, drought, and heat. The MtCAD and LjCAD expressed highly in stress-responsive tissues such as nodule, root, immature flower, seed, and leaf. Meanwhile, RNA-sequencing data further highlighted several potential stress-responsive genes. In M. truncatula , The MtCAD1 , MtCAD3 , MtCAD9 , MtCAD15 , MtCAD23 , MtCAD27 , and MtCAD47 exhibited higher expression under cold, drought, and freezing stress compared with control conditions. Whereas in L. japonicus , LjCAD6 , LjCAD8 , and LjCAD11 showed higher expression under cold, drought, and heat stress. Thus, these genes may serve as promising candidates for improving abiotic stress tolerance and provide molecular insights into their functional roles for future crop improvement programs and experimental validation.